2000
DOI: 10.1093/aler/2.1.170
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of adversarial versus inquisitorial procedural regimes

Abstract: This article reports the results of a multiyear series of economic experiments comparing the two dominant types of legal procedures used in adjudication: (1) the "adversarial" model of party-controlled procedure versus (2) the "inquisitorial" model of judge-controlled procedure. The principal finding is that the relative fact-finding efficiency of the two systems, in terms of both the "revelation" of hidden facts and the "accuracy" of decision, depends significantly upon the information structure. Under a "pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Block et al (2000) consider an experimental design in which one party is right and the other is wrong (so that evidence, if it is available, is conclusive) 109 . They consider two scenarios; one in which Mr Wrong has private information to the effect that he is wrong and one in which, in addition, Mr Right also has a hint that he is right.…”
Section: Adversarial Versus Inquisitorialmentioning
confidence: 99%
“…Block et al (2000) consider an experimental design in which one party is right and the other is wrong (so that evidence, if it is available, is conclusive) 109 . They consider two scenarios; one in which Mr Wrong has private information to the effect that he is wrong and one in which, in addition, Mr Right also has a hint that he is right.…”
Section: Adversarial Versus Inquisitorialmentioning
confidence: 99%
“…Frase (1998) also discusses the inquisitorial trial system in criminal matters, and legal analyses of continental trial procedures are found in Mack (1996) and Moskovitz (1995). Finally, those interested in experimental research into the merits of the two trial systems should peruse Block and Parker (2004) and Block et al (2000; see also Deffains and Demougin 2008).…”
Section: The Adversarial Versus the Inquisitorial Systemmentioning
confidence: 99%
“…First, experimental evidence indicates that the adversary system may be superior to the inquisitorial system in mitigating any decisionmaker biases 11 (Thibaut et al 1972;Block et al 2000). Thus, where a decisionmaker is based, the adversary system may improve accuracy of outcomes.…”
Section: Adversary V Inquisitorial Systems Compared: a Second Lookmentioning
confidence: 99%
“…Instead, their relative accuracy depends critically on the type of information in question, e.g., how difficult it is to uncover, the degree of asymmetry between the parties in the amount of relevant information that they hold, and the degree to which one party has some sense of the information possessed by the other party (Block et al 2000;Block and Parker 2004). Experimental research suggests that lawyers in an adversarial system may work harder and will produce more information than judges in an inquisitorial system.…”
Section: Adversary V Inquisitorial Systems Compared: a Second Lookmentioning
confidence: 99%